Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.46747/cfp.6705345
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning

Abstract: Do not delay advance care planning (ACP) conversations.Recall and describe a clinical encounter in which you were called on to choose wisely I recently accepted the wife of one of my patients into my practice. They are both in their 80s, very independent, and fearful of coronavirus disease 2019 (COVID-19). In our meet and greet, while updating her profile in her electronic medical record (EMR), I broached the topic of ACP. While she had previously been very healthy, owing to the uncertainty surrounding the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The importance of ACP and ongoing communication between older persons, their families and healthcare professionals is progressively becoming recognised (Sellars et al 2015;Amjad et al 2014;Baughman et al 2014;in der Schmitten et al 2014;Stone et al 2013;Storey and Sherwen 2013) especially in Australia (Bird 2014). However, evidence persists that initiating ACP discussions with residents of RACFs remains difficult for staff (Boot and Wilson 2014;Dempsey 2014;Schubart et al 2014;Robinson et al 2013;Stone et al 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance of ACP and ongoing communication between older persons, their families and healthcare professionals is progressively becoming recognised (Sellars et al 2015;Amjad et al 2014;Baughman et al 2014;in der Schmitten et al 2014;Stone et al 2013;Storey and Sherwen 2013) especially in Australia (Bird 2014). However, evidence persists that initiating ACP discussions with residents of RACFs remains difficult for staff (Boot and Wilson 2014;Dempsey 2014;Schubart et al 2014;Robinson et al 2013;Stone et al 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature sheds light on the opportunities to incorporate health educators and coaches to strengthen PA promotion in clinical settings 11. Sports and exercise specialists, including sports and exercise physicians and allied health teams, can contribute their expertise to promote PA in clinical settings 12 13. Another approach is PA referral schemes, established in several countries to connect patients with PA professionals or exercise specialists 14.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Sports and exercise specialists, including sports and exercise physicians and allied health teams, can contribute their expertise to promote PA in clinical settings. 12 13 Another approach is PA referral schemes, established in several countries to connect patients with PA professionals or exercise specialists. 14 However, each country has different characteristics and roles of the health system and sports and exercise specialists.…”
Section: Introductionmentioning
confidence: 99%
“…2 ACP has a more immediate relevance for those with life-limiting conditions and offers structure for the consideration and communication of care preferences to loved ones and caregivers. 3…”
Section: Introductionmentioning
confidence: 99%
“…2 ACP has a more immediate relevance for those with life-limiting conditions and offers structure for the consideration and communication of care preferences to loved ones and caregivers. 3 Teixeira and colleagues 6 reported on the general experience of Canadians (aged 18 to >65 years) with ACP. Consistent with the findings above, they found that few Canadians (16%) knew the term 'Advance Care Planning', and slightly over half (52%) of respondents had engaged in any discussions with family or friends about healthcare treatment preferences in the event that they became too ill or injured to speak for themselves; only 10% had ACP discussions with healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%